Chemical Constituents of Prunus persica Stem Bark - Raturi, R.; Sati, S. C.; Badoni, P. P.; Singh, H.; Sati, M. D. (Journal of Scientific Research, 2012)
Chemical examination of methanolic extract of Prunus persica, stem bark, led to isolation of Flavon 3', 4', dihydroxy 6 methoxy 7-O-? -L-rhamnopyranoside (1), Prunetin-5-O-?-D-glucopyranoside (2), with previously known compounds ?-Sitosterol and Querceitin. Compounds 1 and 2 were isolated for the first time from this plant. The structure of compounds were elucidated with the help of chemical and spectral studies. © 2012 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v4i3.7725 J. Sci. Res. 4 (3), 769-774 (2012)